Usability Evaluation and Interface Design Improvement for the Maxim Application with User-Centered Design Approach - Rajendra Daniel Saksono; Dinar Sulistyorini; Syifa Rizka Sagita; Kasiyah; Lia Sadita (Jurnal Sistem Informasi, 2024)
The research focused on the user interface of the Maxim application, a ride-hailing service in Indonesia facing usability challenges compared to its competitors, such as Gojek, Grab, and inDrive. The study aimed to identify user issues and propose alternative interface designs to enhance usability. The User-Centered Design (UCD) approach was adopted, involving two iterative phases that yielded high-fidelity designs. Through online surveys and interviews, 77 problem categories were identified, adhering to Usability Heuristic principles, and 93 design solutions were crafted based on Shneiderman's Eight Golden Rules of Interface Design. Subsequently, the design solutions were evaluated through moderated usability testing (UT) and the System Usability Scale (SUS) questionnaire distribution. The second iteration's UT results indicated improved success rates, reduced task completion times, higher SUS scores, and positive user feedback on ease of use. In conclusion, this research improved the application's usability and offered valuable recommendations for further enhancements and future investigations.